Existência e concentração de soluções para uma equação de schrödinger estacionária - Padovani Ederli, Jonas Antonio [UNESP] (2015)
In this work we study some results about existence and concentration of positive solutions for a nonlinear stationary version of the Schrödinger equation, as a parameter goes to zero. More speci cally, we prove that the sequence of solutions have a maximum points which concentrate around the global minimum of the potential, as a parameter goes to zero. The technique used relies on variational methods to compare the solutions with the solution of a limit problem which have information on the minimum of the potential